Performance Anthology : Source Book for a Decade of California Performance Art - Barry, Judith; Frye Burnham, Linda; Kaprow, Allan; Loeffler, Carl E.; Marioni, Tom; Roth, Moira; Tong, Darlene (San Francisco : Contemporary Arts Press, 1980)
Alpert, Richard ; Ant Farm ; Antin, Eleanor ; Banana, Anna ; Best, Paul ; Beuys, Joseph ; Blanchard, Nancy ; Bob & Bob ; Brown, Francis ; Buchanan, Nancy ; Burden, Chris ; Cazazza, Monte ; Chang, Kathleen ; Cleveland, Buster ; De Cointet, Guy ; Costello, K.P. ; Costello, Kevin ; Cotton, Paul ; Darling, Lowell ; Deak, Norma Jean ; DeMarinis, Paul ; Duncan, John ; Eva Sisters ; Forte, Paul ; Fox, Terry ; Freilicher, Melvyn ; Fried, Howard ; Gaglione, Bill ; Garner, Phil ; Gaulke, Cheri ; Griffin, Eileen ; Hak Kyung Cha, Theresa ; Hall, Doug ; Henderson, Mel ; Hershman, Lynn ; Hershmann, Lynn ; Howard, Barbara ; Ireland, David ; Jones, Kim ; Kaprow, Allan ; Kipper, Harry ; Klick, Laurel ; Kos, Paul ; Labowitz, Leslie ; Lacy, Suzanne ; Laub, Stephen ; Loeffler, Carl ; Lord, Chip ; Marioni, Tom ; Markowitz, Barry ; McCarthy, Paul ; Melchert, Jim ; Mogul, Susan ; Montano, Linda ; Morrison, Bill ; Motion ; Nauman, Bruce ; Newton, Richard ; Oliveros, Pauline ; Pomeroy, Jim ; Quinn, Aysha ; Rapaport, Debra ; Rosenthal, Rachel ; Rosler, Martha ; Ruppersberg, Allen ; Sapien, Darryl ; Scott, Jill ; Seemayer, Stephen ; Sekula, Allan ; Sherk, Bonnie ; Smith, Alexis ; Smith, Barbara ; Smith, Brad ; Sturgeon, John ; Tepper, Irv ; The Waitresses ; Uthco, T.R. ; Le Va, Barry ; Vokietaitis, Constancia ; White, John ; Wick, Susan ; Wilding, Faith ; Wilhite, Bob ; Winder Baker, Mary ; Wise, Nina
Engels
boek
Keywords: California